2022
DOI: 10.1186/s40104-022-00751-x
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the architecture of human-induced polygenic selection in Duroc pigs

Abstract: Background As one of the most utilized commercial composite boar lines, Duroc pigs have been introduced to China and undergone strongly human-induced selection over the past decades. However, the efficiencies and limitations of previous breeding of Chinese Duroc pigs are largely understudied. The objective of this study was to uncover directional polygenic selection in the Duroc pig genome, and investigate points overlooked in the past breeding process. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Additionally, teat number and backfat thickness displayed noteworthy loci, such as 7_97614602, with a genetic correlation of −0.3068. This indicated that these SNPs possess the potential to influence a multitude of intricate traits [ 22 ]. Consequently, these SNPs warrant further scrutiny in the context of breeding programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, teat number and backfat thickness displayed noteworthy loci, such as 7_97614602, with a genetic correlation of −0.3068. This indicated that these SNPs possess the potential to influence a multitude of intricate traits [ 22 ]. Consequently, these SNPs warrant further scrutiny in the context of breeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…Different breeds each possess distinct features, and there exists a discrepancy in breeding goals. Specifically, the Duroc breed exhibits rapid growth, efficient feed utilization, and a high percentage of lean meat in the carcass, making it commonly used for terminal sires [ 22 ]. On the other hand, Landrace pigs are known for their excellent reproductive performance and have a high number of piglets per litter; this breed is commonly employed as the maternal line in commercial herds [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first step in building the ideal individual is to identify the advantageous traits in the parent breed. Different pig breeds have specific advantages; the advantageous traits of Chinese indigenous pigs are mainly in meat quality, roughage tolerance, and disease resistance, while that of the introduced breeds has better leanness, growth rate, and feed conversion ratio [ 15 ]. The beneficial genotype corresponding to the desired trait is identified after the determination of the advantageous trait.…”
Section: Methodsmentioning
confidence: 99%